Формирование способности определять течениевремени в различных видах деятельности у детей с умственной отсталостью - Марукян, В. С.
In this article we experimentally just ify the possibility of forming ability to determine time periods in diff erent types of activities for children with mental retardation.
Keywords: Дети с умственной отсталостью